(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The derivation of kinetic equations for the oxidation processes by the free-radical nonbranched-chain mechanism is shown. This derivation is based on the proposed reaction scheme for the initiated addition of free radicals to the multiple bond of the molecular oxygen includes the addition reaction of the peroxyl free radical to the oxygen molecule to form the tetraoxyl free radical. This reaction competes with chain propagation reactions through a reactive free radical. The chain evolution stage in this scheme involves a few of free radicals, one of which (tetraoxyl) is relatively low-reactive and inhibits the chain process by shortening of the kinetic chain length. The rate equations (containing one to three parameters to be determined directly) are deduced using the quasi-steady-state treatment. The kinetic description with use the obtained rate equations is applied to the γ-induced nonbranched-chain processes of the free-radical oxidation of liquid o-xylene at 373 K and hydrogen dissolved in water containing different amounts of dioxygen at 296 K. The ratios of rate constants of competing reactions and rate constants of addition reactions to the molecular oxygen are defined. In these processes the oxygen with the increase of its concentration begins to act as an oxidation autoinhibitor (or an antioxidant), and the rate of peroxide formation as a function of the dissolved oxygen concentration has a maximum. It is shown that a maximum in these curves arises from the competition between hydrocarbon (or hydrogen) molecules and dioxygen for reacting with the emerging peroxyl 1:1 adduct radical. From the energetic standpoint possible nonchain pathways of the free-radical oxidation of hydrogen and the routes of ozone decay via the reaction with the hydroxyl free radical in the upper atmosphere (including the addition yielding the hydrotetraoxyl free radical, which can be an intermediate in the sequence of conversions of biologically hazardous UV radiation energy) were examined. The energetics of the key radical-molecule gas-phase reactions is considered.